2014
DOI: 10.1016/j.annemergmed.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Intravenous Antivenom Versus Placebo for Latrodectism: The Second Redback Antivenom Evaluation (RAVE-II) Study

Abstract: 1 Randomized controlled trial of intravenous antivenom versus placebofor latrodectism: the second redback antivenom evaluation (RAVE-II) study. AbstractObjective: Latrodectism is the most important spider envenomation syndrome worldwide.There remains considerable controversy over antivenom treatment. We aimed to investigate whether antivenom resulted in resolution of pain and systemic effects in patients with latrodectism given standardized analgesia.Methods: In a multicentre randomized placebo-controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
1
45
0
1
Order By: Relevance
“…The VAS is one of the most commonly used, including in earlier studies of blue bottle stings 1 and red‐back spider bites 10 . More recent studies have employed a verbal numerical rating score because it is easier to administer (paper is not required) 11 and it is used in clinical practice; management of C. fleckeri stings should now include regular assessment of the pain with the verbal numerical score. Correcting for the baseline pain score is controversial, but it enables comparison of patients with differing severity of subjective pain, and this approach has been applied in three previous studies of painful envenoming syndromes 1 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The VAS is one of the most commonly used, including in earlier studies of blue bottle stings 1 and red‐back spider bites 10 . More recent studies have employed a verbal numerical rating score because it is easier to administer (paper is not required) 11 and it is used in clinical practice; management of C. fleckeri stings should now include regular assessment of the pain with the verbal numerical score. Correcting for the baseline pain score is controversial, but it enables comparison of patients with differing severity of subjective pain, and this approach has been applied in three previous studies of painful envenoming syndromes 1 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…From an efficacy perspective, there are reports that the overseas commercial product was effective in patients with bites from not only redback spider but also other spider species (28)(29)(30)(31)(32)(33)(34)(35). However, there are also conflicting reports that the use of antivenom is not significantly effective in treating patients with bites when an analgesic is used in combination or when an analgesic is the primary treatment choice (36,37). Therefore, future clinical applications should take these aspects into account.…”
Section: Discussionmentioning
confidence: 99%
“…52 In 2014, Isbister et al conducted a RCT to evaluate the effect of redback antivenom, and concluded that the addition of antivenom to standardized analgesia in patients with latrodectism did not significantly improve pain or systemic effects. 53 However, that study has raised some concerns. In Australian emergency departments, some patients with redback spider bites, including children, pregnant women, and the elderly, have increased risks of developing severe or systemic symptoms and are more likely to receive antivenom.…”
Section: Redback Spider (Latrodectus Hasselti) Bitesmentioning
confidence: 99%